BRIDGING THE THEORY-PRACTICE GAP: THE IMPACT OF SCHOOL FIELD IMPLEMENTATION ON THE TEACHING READINESS OF PROSPECTIVE ECONOMICS TEACHERS - Silalahi, Agnes Kezia; Mifrasah, Emy (Edunomika Journal : Studies In Education And Development Economics, 2026)
The gap between mastery of pedagogical theory and practical competency in the classroom remains a fundamental challenge in global teacher education. This study aims to analyze the effect of the School Field Introduction (PLP) program as a new policy instrument to bridge this gap on the teaching readiness of prospective teacher students. Using a quantitative approach with an ex-post facto design , this study involved 97 Economics Education students from the 2016 intake of the University of Jambi as respondents. Data were collected through a validated questionnaire instrument and analyzed using simple linear regression. The results empirically prove that PLP has a positive and significant influence on teaching readiness, with a regression coefficient of 0.579 and a high significance value. These findings indicate that direct immersion experiences in schools through cultural observation, assistance, and guided practice play a vital role in transforming declarative knowledge into procedural knowledge and increasing the self-efficacy of prospective teachers. The novelty of this study lies in evaluating the impact of the implementation of the latest teacher education standards regulation (Permenristekdikti No. 55/2017) in the specific context of economics education. This research contributes to the education literature by confirming that PLP is not simply a curricular routine, but rather a key determinant of teacher professionalism. Consequently, Teacher Training Institutions (LPTK) need to strengthen the quality of mentoring during PLP to ensure adaptive and competent graduates.